Zero-waste multistage utilization of dandelion root - Fang, Yongwei; He, Aimin; Chen, Weihua; Jia, Xiaohui; Zhao, Mingqin; Lai, Miao; Zhang, Hong (Frontiers in Chemistry, 2024)
In the fragrance and perfume industry, the controlled release of fragrances are crucial factors that contribute to consumer appeal and product quality enhancement. In this study, various aromatic active substances were extracted from dandelion root (DR), which was subsequently calcined to produce high-performance porous biochar material. The dandelion root biochar (DRB) material was identified as promising adsorbents for the controlled release of fragrances. Furfuryl alcohol was chosen as the model fragrance for inclusion and controlled release studies. The DRB exhibited a substantial specific surface area of 991.89 m 2 /g, facilitating efficient storage and controlled release capabilities. Additionally, the DRB's high stability and porous nature facilitated rapid collection and efficient recyclability. This research significantly contributes to the development of a sustainable, zero-waste multistage utilization strategy for dandelion roots, indicating a potential applications in the food flavoring industry and environmental conservations.